The Economic, Moral and Spiritual Accountability at Kamaran Villa Business and It’s Relevance in a Suluk Linglung Sunan Kalijaga - Mennita, Ria; Soeherman, Bonnie (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Tourism Area of Prigen or Prigen Village is a area where “Kamaran” Villa business operates in Pasuruan Regency. Kamaran Villa is a villa that provides rental services per room, either short time or full time. Business of “Kamaran” Villa presents pros and cons on its accountability reality. This research aims to uncover the economic, moral and spiritual accountability of Villa Kamaran business, to interpret it and to serve it with the teachings in the Suluk Linglung Sunan Kalijaga. This research is a qualitative study with the Phenomenology approach. The results showed that this business could be accountable economically, but could not be accountable morally and spiritually. The teachings in the Suluk LingLung Sunan Kalijaga, which is the colors of lust in the human body can reflect the factors that affecting the acceptance and assessment of the owner and Prigen’s people to business accountability of “Kamaran” Villa. The value in Suluk Linglung is able to bring the achievement of an accountable business where accountability must lead to worship and not prioritize on worldly gains.